1977
DOI: 10.1051/jphys:01977003805045900
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance in low-temperature electron-irradiated diamond

Abstract: A man-made boron doped diamond has been irradiated at 77 K with 1.5 MeV electrons. After irradiation an isotropic signal is observed which is composed of a central resonance at g = 2.00 and of a two line spectrum (A 7) split symmetrically 60 G from the central line. After sufficient annealing an additional two line spectrum (A 8) split symmetrically 33 G from the central line appears. The variation with dose and with isochronal annealing (up to 330 K) of these spectra is measured. Their annealing behaviour is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1979
1979

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…This suggests that highly disordered regions, which are created by each impinging ion, overlap when the dose is large enough and form a continuous layer. Morhange et alfound similar annealing behaviour as Brosious et al(1974a). Brosious et al(1974b) found that if the nitrogen ions are implanted at high temperatures (2: 600 "C) the spectra appear to be a superposition of two signals.…”
Section: Defects Introduced By Ion Implantation In Diamondmentioning
confidence: 76%
“…This suggests that highly disordered regions, which are created by each impinging ion, overlap when the dose is large enough and form a continuous layer. Morhange et alfound similar annealing behaviour as Brosious et al(1974a). Brosious et al(1974b) found that if the nitrogen ions are implanted at high temperatures (2: 600 "C) the spectra appear to be a superposition of two signals.…”
Section: Defects Introduced By Ion Implantation In Diamondmentioning
confidence: 76%